Genomic Selection models for the 3K SNP-Seek set for 1) grain Zn concentrations and 2) yield under low-fertility conditions in Madagascar. - CGIAR Research Program on Rice (2021)
Five donors have have been utilized in the development of new breeding populations. Tanaka R, et al, (2021) From gene banks to farmer’s fields: Using genomic selection to identify donors for a breeding program in rice to close the yield gap on smallholder farms. Theoretical and Applied Genetics 134:3397–3410.